Successful diagnosis and treatment of pulmonary aspergillosis-related malignant catatonia using propofol and quetiapine: A case report. Issue 19 (14th May 2021) - Nomura, Kazuhito; Sakawaki, Sonoko; Sakawaki, Eiji; Yamaoka, Ayumu; Aisaka, Wakiko; Okamoto, Hiroyuki; Takeyama, Yoshihiro; Uemura, Shuji; Narimatsu, Eichi
Abstract: Introduction: Malignant catatonia (MC) is a movement disorder syndrome characterized by immobility, rigidity, and consciousness disorders that develops in association with mental and physical diseases. It is often fatal due to hyperthermia, rhabdomyolysis, and acute kidney injury. Its clinical symptoms are similar to those of another disorder, neuroleptic malignant syndrome (NMS), and it is often difficult to distinguish between the 2 disorders. Patient concerns: An Asian woman in her 60s with history of schizophrenia. She was admitted to our hospital because of symptoms such as fever, unconsciousness, and muscle rigidity. Blood tests showed kidney injury and high creatinine kinase levels. Diagnoses: At the time of admission, she had been diagnosed with NMS complicated by pulmonary aspergillosis and was undergoing treatment although there was no improvement. Interventions: Subsequently, the administration of propofol, a gamma-aminobutyric acid A agonist, markedly improved the symptoms, and the diagnosis was corrected to MC. At the beginning of her hospitalization, she received dantrolene, bromocriptine, amantadine, and L-3, 4-dihydroxyphenylalanine as treatment for NMS, but her symptoms did not improve. With propofol, which is used for sedation, her catatonic symptoms improved markedly. Quetiapine administration further improved the symptoms, and it eventually resolved completely. Outcomes: The patient's MC was in remission. Prolonged intensive care management resulted in a decline in activities of daily living, and she required rehabilitation at another hospital. Conclusion: This is the first report of MC with suspected involvement of pulmonary aspergillosis. MC differs from NMS, in that it is treated more effectively with gamma-aminobutyric acid A agonists. Although benzodiazepines are the first choice for the diagnosis and treatment of MC, they are ineffective for majority of patients with schizophrenia. However, even in such cases, propofol and quetiapine are effective, and they facilitate diagnosis and treatment.